Perfil de ácidos graxos, propriedades nutricionais e estabilidade oxidativa de manteigas do leite de vacas alimentadas com cana-de-açúcar suplementada com óleo de girassol - Patricia Aparecida Vieira de Barros (2011)
The objective of this study was to evaluate the profile of fatty acids (FA), the nutritive quality and the oxidative stability (OE) of butter made with milk from cows fed with sugar cane 0 (T0); 1.5 (T1.5); 3.0(T3.0) and 4.5% (T4.5) of sunflower oil (SO). A randomized 4 x 4 Latin Square (LS) design was used, each period consisting of 10 days of cows diet adaptation and, one day of sample collection. Butters were produced in an artisanal way with milk from every treatment (total of 16 butters). The butters were analyzed for the fatty acids profile by GC-FID and for the physic-chemical characteristics according to official methods. The fatty acid profile was used for the calculation of some nutritional parameters, among them, indexes of atherogenicity, thrombogenicity, and omega-6/omega-3 and hypocholesterolemic/hypercholesterolemic ratios. There was a reduction (P <0.05) on the proportion of the FA lauric (C12), myristic (C14) and palmitic (C16) of 53, 34 and 39%. There was also a linear increase (P <0.05) of 867, 687, 148% on the proportion of the FA conjugated linoleic acid (C18:2 cis-9 trans-11), vaccenic (C18:1 trans-11) and oleic (C18:1cis-9), respectively, with supplementation of T0 to T4.5. With respect to the nutritional quality of the butters, there was a linear decrease (P <0.05) on the atherogenicity (4.02, 2.70, 1.80 and 1.41) and thrombogenicity indexes (4.68, 3.43, 2.50 and 2.05) and there was a linear increase (P <0.05) ion the hypocholesterolemic/hypercholesterolemic ratio (0.30, 0.45, 0.62, 0.70) with the increase of SO to the cows diet. The oxidative stability of the butter was 4.0, 3.03, 2.42 and 1.68 h, respectively, for T0, 1.5, 3.0 and 4.5. The increased SO in the cows diet provided butter with an improved FA profile with regard to nutritional value for human health; however, there was a decrease on the butter of the shelf life.